2021
DOI: 10.1002/jsfa.11691
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical characterization and linear epitopes identification of arginine kinase allergen from Crassostrea gigas

Abstract: BACKGROUND Molluscan shellfish, including oysters, often cause allergic reactions in sensitive people throughout the world. It has been demonstrated that arginine kinase (AK) is one of the major allergens of oyster. The present study aimed to evaluate the immunoreactivity and structure of oyster AK as affected by heat treatment, pH change, and in vitro digestion. What is more, the immunoglobulin E‐binding epitopes of this allergen were also predicted and validated. RESULTS Thermal and pH assays revealed that A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Among the linear epitopes identified in this study, L-Cra a 2-2 partially overlapped with the linear epitopes of Crassostrea gigas AK, Scylla paramamosain AK, and L. vannamei AK. Among the four identified conformational epitopes, C-Cra a 2-4 is partially consistent with conformational epitopes of S. paramamosain AK (I 121 H 185 ­K 189 G 310 T 311 R 312 ­T 316 A 318 E 319 G 320 ­V 322 ), indicating that epitopes of AK are conserved among crustaceans and mollusks .…”
Section: Discussionmentioning
confidence: 54%
“…Among the linear epitopes identified in this study, L-Cra a 2-2 partially overlapped with the linear epitopes of Crassostrea gigas AK, Scylla paramamosain AK, and L. vannamei AK. Among the four identified conformational epitopes, C-Cra a 2-4 is partially consistent with conformational epitopes of S. paramamosain AK (I 121 H 185 ­K 189 G 310 T 311 R 312 ­T 316 A 318 E 319 G 320 ­V 322 ), indicating that epitopes of AK are conserved among crustaceans and mollusks .…”
Section: Discussionmentioning
confidence: 54%
“…This result revealed the existence of generally strong cross‐reactivity of the 42 and 49 kDa bands between P. polita and sea snail C. obtusa , whereas moderate cross‐reactivity was observed between P. polita and the other shellfish extracts tested, suggesting the presence of homologous epitopes between P. polita and C. obtusa and the existence of species‐specific epitopes between P. polita and the other shellfish tested. Additionally, the 42 kDa band might consist of several different proteins at the same molecular weight with different allergenic properties, probably arginine kinase, which had been documented as a pan‐allergen in molluscan and crustacean shellfish 19,27,44 . It was interesting to note that the IgE reactivity in one of the sera tested (patient 4) showed an exclusive IgE cross‐reactivity pattern compared with the other sera tested: almost no inhibition reactivity was observed for P. polita against P. monodon , S. olivacea , and L. edulis extracts, but high cross‐reactivity was present with C. obtusa extract, indicating that this patient was highly reactive to only snail allergens, probably due to snail mono‐sensitivity 45…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, the 42 kDa band might consist of several different proteins at the same molecular weight with different allergenic properties, probably arginine kinase, which had been documented as a pan-allergen in molluscan and crustacean shellfish. 19,27,44 It was interesting to note that the IgE reactivity in one of the sera tested (patient 4) showed an exclusive IgE cross-reactivity pattern compared with the other sera tested: almost no inhibition reactivity was observed for P. polita against P. monodon, S. olivacea, and L. edulis extracts, but high cross-reactivity was present with C. obtusa extract, indicating that this patient was highly reactive to only snail allergens, probably due to snail mono-sensitivity 45 The findings in this study support a previous report from Emoto et al 18 that indicated IgE cross-reactivity is recognized among molluscs, among crustaceans, and between molluscs and crustaceans. The primary structures of crustacean tropomyosin were proved to share more than 90% sequence identity with one another, except for some species showing 60% sequence identity of tropomyosin with other shellfish.…”
Section: Wileyonlinelibrarycom/jsfamentioning
confidence: 99%
See 2 more Smart Citations